PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI DAN KEPUASAN KERJA SERTA KINERJA KARYAWAN PT PUPUK KALIMANTAN TIMUR TBK - abdul choliq hidayat (Universitas Ahmad Dahlan, 2018)
The purposes of this research were to examine and analyze the influence of the following variables: 1. Leadership Style on Work Motivation; 2. Leadership Style on Job Satisfaction; 3. Leadership Style on Employee Performance; 4. Work Motivation on Employee Performance; 5. Job Satisfaction on Work Motivation; and 6. Job Satisfaction on Employee Performance of PT Pupuk Kaltim Tbk.The study was conducted in PT Pupuk Kaltim Tbk in Bontang, East Kalimantan Province. The total number of samples was 168 pairs of questionnaires from 198 packs of respondents and the population consisted of 1,465 employees, obtained by using proportional stratified random sampling. Data analysis used Structural Equation Modelling (SEM), assisted by software program AMOS.Based on research data, analysis and discussion, the results were: The indicators on the variable of leadership style was the orientation of success. The variable of work motivation was the affiliation (arithmetic mean) and competence (confirmatory factor analysis). The variable ofÂ job satisfaction was the company and management. Meanwhile, the variable of employee performance, in which the respondents were supervisors, was the use of time for employees. Leadership style can enhance employee performance through increasing either work motivation or job satisfaction, or increasing both, job satisfaction and work motivation. The employee performance ofÂ PT Pupuk Kaltim Tbk can not be influenced by leadership style directly. It is suggested that the management of PT Pupuk Kaltim Tbk give attention by conducting comprehensive research and scientific steps to make changes in Human Resources Management, especially in revitalizing leadership so that the companyâ€™s objective, vision and mission can be achieved well.